ISLAMIC EDUCATION TEACHERS’ EFFORTS IN DEVELOPING STUDENTS’ SPIRITUAL POTENCIAL IN LEARNING (A STUDY AT SMP N 29 PADANG) - Silvia Susrizal (Ta'dib, 2017)
This study was conducted because of the need to develop students’ spiritual potential in the learning process conducted by teachers of Islamic Education at SMP N 29 Padang. The purpose of this study is to determine the efforts undertaken by teachers of Islamic Religious Education to develop the spiritual potential of students in improving the learning process.In this research, teacher effort in developing potencial student has not  been maximal yet. Aamong the indication is that students have not showed their religious attitude to students either through attitude, behavior, speech or association because the learning model created in the learning process has not given opportunity for students to do so. So that the learning has not given meaning to the students themselves which resulted the ungrowth of the students’ awareness.